1995
DOI: 10.1152/ajpheart.1995.268.3.h987
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of cross bridges in cardiac muscle

Abstract: Tension responses of rat right ventricular trabeculae to fast length changes are measured with microsecond resolution to obtain information about elastic properties of ventricular myocardium. Responses of these isometrically mounted trabeculae at 22 degrees C to fast length changes completed within 30 microseconds at 22 degrees C to fast length changes completed within 30 microseconds were similar in shape to those of skeletal muscle fibers. Results of quantitative evaluation of responses are interpreted in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…However, other experimental evidence has been interpreted as indicating that the crossbridge stroke in cardiac muscle may be as great as 20-30·nm (see De Winkel et al, 1995 and references therein). For instance, De Winkel et al (1995) calculated cross-bridge working stroke from the dynamic stiffness of skinned rat trabelculae (22°C) and concluded that it was at least 20·nm. It has been suggested that these values are consistent with high efficiency values, such as those reported by Peterson and Alpert (1991).…”
Section: Cross-bridge Thermodynamic Efficiencymentioning
confidence: 99%
“…However, other experimental evidence has been interpreted as indicating that the crossbridge stroke in cardiac muscle may be as great as 20-30·nm (see De Winkel et al, 1995 and references therein). For instance, De Winkel et al (1995) calculated cross-bridge working stroke from the dynamic stiffness of skinned rat trabelculae (22°C) and concluded that it was at least 20·nm. It has been suggested that these values are consistent with high efficiency values, such as those reported by Peterson and Alpert (1991).…”
Section: Cross-bridge Thermodynamic Efficiencymentioning
confidence: 99%
“…According to the formula, phase shift is almost zero at frequencies (a<< a) and rises in a transition range around o = ~1 to v n 2-l rad. The empirical formula yields a better description of Young's moduli of the fibre in rigor or in the relaxed state than the five parameter model (Jung et al, 1988) and, in these cases, is almost as good as the seven parameter model used by the same authors to describe the Young's modulus of activated fibres (de Winkel et al, 1993).…”
Section: Calculationsmentioning
confidence: 90%
“…Tension changes following the length change of the muscle fibre are measured by a homemade force transducer with a resonance frequency of 70 kHz in air, a damping time constant of 500 ps and a noise of 2 PV (de Winkel et al, 1993). When the fibre is attached to the transducer the resonance frequency decreases by 5%.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations